Desempenho das funções constitucionais do Poder Legislativo: análise das dimensões promovedora, cooperadora, fiscalizadora, transparente e administrativa da Assembleia Legislativa de Minas Gerais no período de 2011 a 2013 - Jaber, Samy Chafic Abou (2015)
This study investigated the performance of the Legislative Assembly of Minas Gerais, during the period established between 2011 and 2013, with regard to the exercise of its constitutional prerogatives. The methodological tools used consisted of an exploratory study based on bibliographic and documentary research. It was inferred that the legislature functions are not restricted to the duties to legislate and monitor the Executive, but are multifaceted and are supported by lots of interactions with the various actors and institutions, in the legislative arena and in other branches. Being so, the legislative presents different dimensions, such as putting forward laws, cooperate with the Executive, supervise, manage and being transparent. Based on the latest doctrinal studies on the assessment of institutional performance of parliaments and parliamentarians, was developed a new methodology to measure the performance of the Legislative, by drawing up a set of variables and indicators that were able to empirically analyze the case of the legislative of Minas Gerais along the indicated period. It was found that the state legislature had satisfactory results on the "capacities-means" or support. Regarding the essentially constitutional dimensions, it was noted that the parliament of Minas Gerais is active as its legislating role, but not very active about their supervise functions.